Incidence of the Curvature of a Catheter on the Variations of the Inner Volume: Application to the Peripherally Central Catheters. (18th November 2012) - Guiffant, Gérard; Flaud, Patrice; Dantan, Philippe; Dupont, Christian; Merckx, Jacques
Abstract : One particular characteristic of peripherally central catheter (PCC), peripherally inserted central catheter (PICC) or totally implantable venous access device (TIVAD), is to be submitted to a rotational movement around the shoulder in the daily routine. The aim of this paper is to show that these movements induce a variation of the inner volume of the catheter which may be responsible for an internal distal pollution of the lumen. The results are presented in the framework of an open discussion on the catheter protocols of use as well as a possible improvement of the materials.